A CASE STUDY OF SMOKING HABITS AMONG UNIVERSITY STUDENTS IN KARACHI CITY: PREVALENCE AND ASSOCIATED FACTORS - Madiha Kamal; Sara Raiq; Muhammad Asif Shamim; Hira Mujahid (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This research analyzes the prevailing trend of smoking among youth belonging to numerous universities in the metropolitan city of Karachi. The study aims to report the prevalence of student smoking activity by taking several significant factors into account. For primary data collection, a survey questionnaire, containing close-ended questions was floated and responses of 123 students belonging to diverse universities in Karachi were recorded. The findings of the study stressed the conclusion that male students are likely to smoke more as compared to female students. The study also reported significant contributors from other variables like family behavior toward smoking and peer encouragement. Concerning smoking trends, this study shows students' characteristics as well such as smoking 100 cigarettes in life and smoking a whole cigarette in the past 30 days, etc. Other personal opinions and social factors included the reason for smoking, students' attitudes toward smoking on health, perception of having smoke-free public places, and intention to join cessation programs to quit smoking. The study also puts light upon relevant kinds of literature that shows similar indication in this regard.